Occurrences of Lumpy Skin Disease (LSD) in Cattle in Dinajpur Sadar of Bangladesh - Sarkar, Sumon; Meher, Mirza Mienur; Parvez, Mst Misrat Masuma; Akther, Mahfuza (Research in Agriculture Livestock and Fisheries, 2020)
Lumpy skin disease (LSD) is an acute viral disease infectious of cattle and recently emerged very common in Bangladesh causing economic losses. Hence, this study was design to investigate the prevalence of LSD in considering the herd level and some of management status. Thus, a total of 453 sick animals were subjected to study during the period of April 2020 to July 2020 in Dinajpur. LSD was confirmed according to the clinical inspection and microscopic study of skin scraping. The results indicated that the overall prevalence of LSD was 41.06% in cattle. Moreover, the local breed (75%) and young cattle less than one year (64%) were significantly (p<0.001) higher for LSD with the significant (p<0.001) skin lesions in whole body (44%). In addition, the animal grazed in flock (61%), non-dewormed (58%), non-vaccinated (61%) was significantly (p<0.05) higher for LSD. In the same way, 75% prevalence was in without fly repellent (p<0.001). Afterward, the univariate logistic regression in herd level information had the odd ratio of local breed (95% CI: 0.244-0.553), skin lesions in abdominal regions (95% CI: 1.620-5.923) and pregnant cattle (95% CI: 1.057-3.386) was 0.367, 3.098 and 1.892 respectively indicated the likelihood of no LSD outbreaks. Besides this, the odd ratio of dewormed cattle, vaccinated, individually grazed, regular use of disinfectant and fly repellent farm animal was 1.493 (95% CI:1.024-2.177), 1.491 (95% CI:1.020-2.180), 1.656 (95% CI:1.133-2.421), 1.516 (95% CI:0.952-2.414) and 1.660 (95% CI:1.097-2.513), respectively indicated the likelihood of no LSD. Therefore, LSD infection can be greatly reduced by practicing regular vaccination, deworming, and disinfection, vector controlling and allowing grazing individually, especially with great concern to young female cattle of local breed. Res. Agric., Livest. Fish.7(3): 445-455, December 2020